La place des outre-mer du Pacifique dans la stratégie française et l’architecture régionale de sécurité - Caroline Gravelat (Études Caribéennes)
France’s contribution to the security and stability of the Pacific region responds primarily to national needs and neighborhood responsibility. France’s action in the Pacific is part of a complex architecture which combines infranational (French territories), national (Government of the Republic) and supranational (European Union) actors who are autonomous in relation to each other. This network, through which each actor participates, each in their area of expertise, in the regional security architecture implies adaptation, coordination and nuance in the appropriation of action. Two of the three French communities in the Pacific enjoy such a level of autonomy that they can become members of international organizations, after the French government agreement, appoint representatives in the Pacific countries and sign agreements and political commitments, the only limit being the signing of legally binding international treaties for which they must obtain the authorization of Central governement. They can therefore conduct their own diplomacy in virtual freedom. These constraints of ‘sharing sovereignty’ lead us to question the real position of French territories in the Pacific both in national and European strategies as well as in regional architecture.